In-situ X-Ray observations and thermal modeling of unidirectional and bidirectional freeze casting. Issue 9 (1st May 2021) - Yang, Guang; Li, Fangzhou; Xiao, Junfeng; Tetik, Halil; Shah, Nasrullah; Xiao, Xianghui; Li, Jingjing; Liao, Yiliang; Lei, Shuting; Tan, Wenda; Lin, Dong
Abstract: Freeze casting is a cost effective, efficient, and versatile technique capable of producing 3D structures with controlled pore shapes, orientation of crystals, and components' geometries in many porous materials. Freeze casting of hydroxyapatite (HAP) has been widely applied to bone tissue engineering due to HAP's biodegradable, biocompatible, and osteoconductive properties. It provides interconnected porous structures with a relatively high mechanical strength. However, there are still many unexplained phenomena and features because of the complexity of the process. This study demonstrates the use of X-ray synchrotron micro-radiography for providing time-resolved, in-situ imaging of ice crystal growth in the HAP suspensions. The experimental results show the ice crystal growth behavior under unidirectional and bidirectional freeze casting conditions. The finite element modeling (FEM) of the freeze casting process has been used to predict the development of ice front position and temperature gradient in the suspensions during the freeze casting.